On the anisotropic elastic properties of woods - Katz, J. Lawrence; Friis, Lisa; Misra, Anil S.; Marangos, Orestes; Wang, Yong; Spencer, Paulette (My University, 2008)
In 2003 Nature Materials article, Keckes et al. presented deformation properties of a variety of woods in relation to deformation of their individual wood cells. Their point is "The remarkable mechanical properties of biological materials reside in their complex hierarchical structure...". This holds for mineral-based biological materials such as bone as well as for wood. Indeed, one of us (J.L.K.) introduced the concept that to explain the material properties of cortical bone, it was necessary to treat it as a complex material/structural hierarchical composite. Calculations to determine anisotropic properties of bone measured using ultrasonic wave propagation techniques, were extended to similar measurements on both soft and hard woods. These anisotropic properties calculations have been extended to include data based on mechanical measurements of orthotropic elastic constants of both soft and hard woods for comparison with both earlier ultrasonic measurements and mechanical testing on other woods. This work illustrates the fact that understanding and modeling the properties of wood is a complex task as the symmetry changes with scale. For example, lignin is isotropic, hemicellulose and cellulose are transversely isotropic, while the cells and microstructure have orthotropic symmetry. © 2007 Springer Science+Business Media, LLC.
Keywords: Liquid crystals; Mixtures; Thermodynamics